Case Report: A Cryptosporidium infection in a patient with relapsed T‐lymphoblastic lymphoma undergoing allogeneic stem cell transplantation. (17th December 2017) - Schiller, Joanna; Klein, Sebastian; Engels, Marianne; Büttner, Reinhard; Rybniker, Jan; Fätkenheuer, Gerd; Scheid, Christof; Wybranski, Christian; Quaas, Alexander; Reinhardt, Hans Christian; Flümann, Ruth
Abstract: Cryptosporidium infection is a rare cause of enterocolitis. In immunocompromised patients, cryptosporidiosis may lead to debilitating and life‐threatening diarrhea and malabsorption, occasionally with multi‐organ involvement. Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) requires long‐term immunosuppressive therapy, while cellular immunity is usually compromised due to intensive conditioning chemotherapy. Diarrhea in patients who underwent allo‐HSCT may be a sign of an infection, but can also be the result of intestinal graft‐versus‐host disease (GvHD). Here, we describe the case of a patient who developed severe diarrhea following allo‐HSCT for relapsed T‐lymphoblastic lymphoma. Initially, GvHD was suspected and treatment was initiated accordingly. However, a colon biopsy showed signs of cryptosporide oocysts alongside only low‐grade GvHD. Following molecular confirmation of the diagnosis of cryptosporidiosis, an intensive treatment regimen was started. Despite the severe clinical course, the patient recovered and was discharged with only residual symptoms.